ANALISIS DINAMIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI PROVINSI SULAWESI SELATAN: PENDEKATAN ERROR CORRECTION MODEL (ECM) - Caesar Muslim; Muadsim, Ikrar; Saenong, Zainuddin (Journal Economics Technology And Entrepreneur, 2025)
This study analyzes factors influencing poverty in South Sulawesi Province, focusing on the roles of the Human Development Index (HDI), investment, and the Labor Force Participation Rate (LFPR). A quantitative approach is applied using time-series data on the number of poor residents, HDI, domestic investment, and LFPR over a defined observation period. The analysis employs the Error Correction Model (ECM) to capture both short- and long-term relationships among the variables. The results reveal that, in the long run, HDI has a negative and significant effect on poverty, indicating that improving human development quality sustainably reduces the poor population. In contrast, investment and LFPR show no significant long-term impact on poverty reduction. Likewise, HDI, investment, and LFPR are not significant in the short run. These findings highlight the central role of human development policies as a primary strategy for poverty alleviation in South Sulawesi while underscoring the need to optimize investment and labor force contributions.